Carbon capture and storage using low-temperature post-combustion technologies. Issue 24 (17th December 2021) - Rifka, Tala; Morosuk, Tatiana; Tsatsaronis, George
ABSTRACT: To reach the short-term targets of the carbon dioxide limit, measures such as carbon capture and storage are necessary. The objective of this paper is to assess some low-temperature post-combustion technologies for the capture of CO2 from combustion gases. Two methods for the liquefaction and separation of CO2 are discussed: The use of the low-temperature exergy of liquefied natural gas (LNG), while regasifying the LNG, and a refrigeration cycle with helium as the working fluid. Each of these methods is evaluated at three CO2 concentrations: 30%, 13%, and 4%. The results showed that an increase in the concentration of CO2 in the combustion gases causes a large increase in the overall exergetic efficiency and a large decrease in the cost of CO2 capture and energy penalty of the capture process. In addition, these advantages can be seen when the liquefaction method is changed from helium refrigeration cycle to LNG regasification. For a 30% CO2 concentration using LNG, the overall exergetic efficiency is 41.2%, and the cost of CO2 capture is 45.5 $/tCO2 with a CO2 capture rate of 96.3%.